Rotifer synchronous thresholds indicate biodiversity loss below eutrophic classification limits - Rafael L. Macêdo; Karen Costa; Gissell Lacerot; Susana José de Paggi; Juan C. Paggi; Néstor Mazzeo; Mariana Meerhoff; Sarian Kosten; Erik Jeppesen; Christina W. C. Branco (Hydrobiologia, 2026)
Rotifers are diverse bioindicators in shallow lakes, but aggregate metrics can obscure the direction and magnitude of their responses to eutrophication. Here, we analysed rotifer communities across 83 South American shallow lakes spanning a broad eutrophication gradient to interpret taxon-specific contributions to community change. Ten species met stringent identification criteria (purity and reliability ≥ 0.85), with four consistently sensitive (decreasers) and six tolerant (increasers), seven of which belonged to the Brachionidae family. Community thresholds for sensitive taxa occurred under oligotrophic–mesotrophic conditions (lowest along the Toledo index, TSI Tol , at 38.8), preceding conventional than eutrophic classification limits, whereas tolerant taxa shifted under hypertrophic conditions (highest along the Cunha index, TSI Cun , at 59.9). Notably, the threshold for sensitive taxa along Carlson index, TSI Car , was 49, indicating that community decline began during the mesotrophic–eutrophic transition. Community structure did not differ across climatic zones, but overall biodiversity metrics, particularly species richness and taxonomic diversity, were lower above the average community change point, with the strongest decline observed along the Toledo index. Beyond underscoring the importance of local environmental factors and trophic index selection, we recommend taxon-specific threshold analyses on time series within regions to evaluate the consistency of ecological thresholds across broad latitudinal gradients. We further recommend that monitoring programs incorporate rotifer abundance and frequency as sensitive early indicators of eutrophication.